Construction of Experiential in the News Text of the Inauguration of Members of the MPR/DPR/DPD RI 2024-2029 - Astri, Nanda Dwi; Mulyadi, Mulyadi (RIRAI Publisher, 2024)
This study examines the construction of experiential in the news text of the inauguration of members of the MPR/DPR/DPD RI for the period 2024-2029. The construction of experiential is a morphosyntactic construction where the subject experience something, feels a sensation, and experiences mental actions by the stimulus of the sentence object. The steps in this research method are carried out with the aim of finding structured, concrete answers through language phenomena that can be studied. Data collection was conducted using the observation method and note-taking technique. Data analysis was conducted using the distribution method and basic techniques for direct elements and advanced techniques of reading, marking, expanding, and changing forms. The results of this study show that the construction of experiential can be analyzed in the verbs of affection and verbs of cognition. The agent occupies the position of the subject mapped as the experiential or the object mapped as the stimulus or both can correspond in the sentence. The verbs of affection can involve or describe someone's feelings. In addition, the addition of two verb arguments can change the semantic role in the example of the verb